Association between household socioeconomic level and consumption of fast food and soft drinks: A cross-sectional assessment of the Young Lives cohort in Peru - Najar, Carol Argelia (2020)
Introduction: The consumption of fast food and soft drinks is a risk factor for developing overweight and obesity. This study aimed at assessing if there is association between household socioeconomic level and the consumption of fast food and soft drinks among children. Material and Methods: A cross-sectional assessment of the data from the third round (2009-2010) of the youngest cohort of the Young Lives study in Peru was conducted. Sampling was conducted in three stages: In the first one, the country was divided into equal geographical regions, excluding the 5% of the richest district; in the second stage, 20 sentinel sites were chosen and an area within each sentinel site was selected. Finally, in the third stage, eligible children were selected. Outcomes were the self-reported consumption of fast food and soft drinks (never, sometimes, and always), whereas the exposure was household socioeconomic status (in quintiles). Crude and adjusted models were created between variables of interest using Poisson regression models, with robust variance, to report prevalence ratios (PR) and 95% confidence intervals (95% CI). Results: Data of 1901 children, of which 942 (49.6%) were girls, with a mean age of 7.5 (SD: 0.5) was analyzed. A total of 24.1% (95%CI: 22.2%-26.1%) reported always consuming fast food, whilst this number was 22.4% (20.5%-24.3%) for soft drinks. Compared to the lowest socioeconomic quintile, those who were in higher socioeconomic status had more probability of consuming fast food and soft drinks (Chi-squared for trends <0.001). The highest socioeconomic quintile had a greater probability to always consume fast food (PR=1.42; 95%CI: 1.08-1.88) and soft drinks (PR=1.71; 95%CI: 1.24-2.37). Conclusions: This study shows that there is a significant association between the household socioeconomic level and the consumption of soft drinks and fast food.